2011
DOI: 10.1093/humrep/der405
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic stress simultaneously stimulates vascular endothelial growth factor via hypoxia-inducible factor-1  and inhibits stromal cell-derived factor-1 in human endometrial stromal cells

Abstract: Hypoxia simultaneously acts to increase VEGF via HIF-1α and to decrease SDF-1 in a HIF-1α-independent manner in ESCs. These results indicate a potential mechanism for the action of hypoxic conditions that could influence angiogenesis in the human endometrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 37 publications
6
45
0
5
Order By: Relevance
“…Hypoxia attenuates the expression and production of SDF‐1 in ESC in a time‐dependent manner . Similar changes have been observed in ESC following stimulation with the hypoxia‐mimicking agent CoCl 2 in a dose‐dependent manner.…”
Section: Sdf‐1supporting
confidence: 70%
See 2 more Smart Citations
“…Hypoxia attenuates the expression and production of SDF‐1 in ESC in a time‐dependent manner . Similar changes have been observed in ESC following stimulation with the hypoxia‐mimicking agent CoCl 2 in a dose‐dependent manner.…”
Section: Sdf‐1supporting
confidence: 70%
“…Hypoxia‐inducible factor‐1α has also been shown to bind directly to the hypoxia‐response elements (HRE) in the promoters of the genes encoding VEGF. We confirmed that hypoxia‐induced VEGF secretion was significantly attenuated by echinomycin . Echinomycin is a sequence‐specific DNA‐binding agent that binds to the HRE site within the promoters of the HIF‐1α target genes and selectively inhibits HIF‐1α binding activity .…”
Section: Vegfsupporting
confidence: 65%
See 1 more Smart Citation
“…These results suggested that resveratrol is involved in a different signaling pathway from HIF‐1α. In addition, increased VEGF production has been observed in ESCs after stimulation with CoCl 2 , a chemical that induces a hypoxia‐like condition by preventing proteasomal degradation of HIF‐1α proteins …”
Section: Discussionmentioning
confidence: 99%
“…The VEGF is a key mediator of physiological and pathological vascular remodeling . It can stimulate the proliferation and migration of endothelial cells, as well as vascular permeability .…”
Section: Functions Of Decidualizationmentioning
confidence: 99%